The core qualities and competencies of the intensive and critical care nurse, a meta‐ethnography. (17th September 2021) - Henriksen, Kjersti Forbech; Hansen, Britt Sætre; Wøien, Hilde; Tønnessen, Siri
Abstract: Aim: To develop a conceptual framework of the core qualities and competencies of the intensive and critical care nurse based on the experiences of intensive care patients, their relatives and the intensive and critical care nurses. Design: Meta‐ethnography. Data sources: A comprehensive, systematic search in seven databases supplemented with hand, citation and reference search. Sources published from 2007 to 2019 were included. Review Methods: Noblit and Hare's understanding of meta‐ethnography and the work of the eMERGE project have directed the synthesis. Results: Nineteen studies were included and synthesized into a conceptual framework. Overarching theme: 'feeling safe and being safe', subtheme: 'creating confidence and motivation' and conceptual categories (CCs): 'technical skills and biophysical knowledge'; 'inter/intra professional teamwork skills'; 'communication skills (with patients and their relatives)'; 'constant and attentive bedside presence'; 'creating participative care'; 'creating confidence through daily care'; 'creating a good atmosphere and having a supportive and encouraging attitude'; and 'building relationship to maintain self‐esteem'. Conclusion: By including the perspectives of intensive care patients, their relatives and intensive and critical care nurses, the core qualities and competencies comprise elements of both patient safety and the feeling of safety. The framework outlines concepts necessary to ensure person‐centred and safe intensive care. Further research should involve each perspective to validate and strengthen the findings. Impact: The development of standards and competence guidelines expressing the learning outcomes and qualification of intensive and critical care nurses should be based on input from intensive care patients, their relatives and intensive and critical care nurses. A variety of core qualities and competencies are necessary to create confidence and motivation, and to make the patient feel safe and be safe. This conceptual framework might form a basis for development of a program or assessment tool to facilitate excellence in education and practice in intensive care.